Pengaruh Pengalaman Pasien Dan Citra Puskesmas Terhadap Kepuasan Pasien Di Puskesmas Batujaya Karawang - Chintia Nurdianty; Ajat Sudrajat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Health is a basic need that is important to be able to live a decent and productive life in everyday life that everyone must have. This study aims to determine the effect of patient experience and image of the health center on patient satisfaction at Puskesmas Batujaya Karawang. The reason this research was conducted was because many people thought that the services and facilities at the puskesmas were poor. The research method used is descriptive verification. The sample of this study was 335 patients at Batujaya Health Center, using incidental sampling. The analytical method used is path analysis and hypothesis testing using the t test and F test and the coefficient of determination. From the test results, all hypotheses can be accepted. The coefficient value of determining patient experience and public health center image on patient satisfaction was obtained by R Squer of 0.544, meaning that 54.4% of patient satisfaction was influenced by these two variables, while 0.456 or 45.6% of patient satisfaction was influenced by other variables not examined in this study. Keywords: Patient Experience, Health Center Image, Patient Satisfaction.